2022
DOI: 10.30659/jpai.5.1.21-31
|View full text |Cite
|
Sign up to set email alerts
|

Kompetensi Kepribadian Guru Dalam Perpektif Muhammadiyah

Abstract: The problems that occur in Muhammadiyah teachers are their behavior that is less moral, has a bad personality, and also weak mastery of religious norms. So this will have an impact on the professionalism of a teacher. What happened to teachers at Muhammadiyah schools was due to the weak mastery and understanding of the personality competencies that a teacher must-have. The method used in this research is the library method, which is a research method whose data sources come from books, scientific articles, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The results of this study have clearly revealed students' assessment of the personality and social competence of Islamic religious education teachers, this can be used as a benchmark by Islamic religious education teachers to improve their competencies and can also help prospective Islamic religious education teachers to prepare themselves (Sasmita & Arqam, 2022). Although student assessments show that Islamic religious education teachers have good personality and social competence, this is not stated 100% of students, meaning that there are still Islamic religious education teachers who do not have good competence, so it is hoped that this research can be evaluation by teachers of Islamic religious education.…”
Section: Social Competence Of Islamic Religious Education Teachersmentioning
confidence: 76%
See 1 more Smart Citation
“…The results of this study have clearly revealed students' assessment of the personality and social competence of Islamic religious education teachers, this can be used as a benchmark by Islamic religious education teachers to improve their competencies and can also help prospective Islamic religious education teachers to prepare themselves (Sasmita & Arqam, 2022). Although student assessments show that Islamic religious education teachers have good personality and social competence, this is not stated 100% of students, meaning that there are still Islamic religious education teachers who do not have good competence, so it is hoped that this research can be evaluation by teachers of Islamic religious education.…”
Section: Social Competence Of Islamic Religious Education Teachersmentioning
confidence: 76%
“…In the learning process between teachers and students there must be interaction. Teachers as educators do not dominate activities, but help create conducive conditions and provide motivation and guidance so that students can develop their potential and creativity through teaching and learning interactions (Sasmita & Arqam, 2022;Sukoyo & Juhji, 2021). Islamic Religious Education teachers are expected to be able to guide students and are also expected to be able to overcome problems that arise in the teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Peraturan Pemerintah Nomor 19 Tahun 2005, pada pasal 28, ayat 3 kompetensi kepribadian ialah kemampuan kepribadian yang mantap, stabil, dewasa, arif, dan berwibawa, menjadi teladan bagi peserta didik, dan berakhlak mulia. Sasmita & Arqam (2022) menyebutkan kompetensi kepribadian mencakup akhlak mulia, arif dan bijaksana, mantap, berwibawa, stabil, dewasa, jujur, menjadi teladan bagi peserta didik dan masyarakat, secara objektif mengevaluasi kinerja sendiri dan siap mengembangkan diri secara mandiri dan berkelanjutan.…”
Section: A Pendahuluanunclassified
“…Kompetensi kepribadian adalah kompetensi yang berkaitan dengan perilaku pribadi guru itu sendiri yang harus memiliki nilai-nilai luhur sehingga terpancar dalam perilaku sehari-hari (Sasmita & Arqam, 2022). Sehingga kompetensi kepribadian ini dijadikan wadah oleh guru dalam berkomunikasi dan berinteraksi pada lingkungan sekitar.…”
Section: Pengaruh Kompetensi Kepribadian Guru Terhadap Peningkatan Mu...unclassified
“…Mujahadah is a method of studying religion and a form of Islamic evangelization that is very important in rebuilding and instilling the human person in order to become a perfect person. It is hoped that they will be able to manage themselves if their background, character, attitude, behavior, mentality, and thinking are in line with the Al-Qur'an and the sunnah since akhlakul karimah will make someone more stable in living this life (Sasmita & Arqam, 2022).…”
Section: A Mujahadah and Syaja'ah Morals In Islammentioning
confidence: 99%